Keberadaan Tari Satai di Pulau Tengah Kecamatan Keliling Danau Kabupaten Kerinci - Dini Noviza; Darmawati Darmawati; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2015)
This study aims to reveal and describe the Satai dance presence in Pulau Tengah, Sub-Regency Keliling Danau, Kerinci Regency. The research is a qualitative research by used analysis descriptive method. The object of research is the Satai dance on Pulau Tengah society. Instrument in this study is the researchers themselves. The type of data used are primary data and secondary data. The data collection techniques performed through the study of literature, direct observation and interviews. Data were analyzed using analysis model of Miles and Huberman. Results of the study found that the Satai dance still encountered in society of Pulau Tengah. Pulau Tengah Society have a high attention to the growth and development of the Satai dance, after is not shown in the ritual of starting reinforcements, in the early 2000s the artists of Pulau Tengah raised Satai dance be welcoming guests. In 2014 the Satai dance changes such as the addition of motion, musical instruments, increasing the number of properties (Carano) and dancers. After changing the function of a means of treatment in the ritual of starting reinforcements become a means of entertainment or spectacle, Satai dance still exist and this proved that Satai dance is always performed in a welcoming ceremony important guests who come to the village of Pulau Tengah in certain events, such as in the race village , appointment depati ninik Mamak, library race, religious gatherings, inauguration of the village head and others. Each year Satai dance is always performed, at least 2 times a year. In the years 2011 to 2015 Satai dance has been shown 10 times. Keyword: Keberadaan, Tari, Satai